Covid Impact On Banking Industry: Research Mapping Using R - Herindar, Evania; Rusydiana, Aam Slamet (El-Barka Journal of Islamic Economics and Business, 2022)
Introduction/Main Objectives: This study intends to evaluate literature studies and determine the evolution of research pertaining to the impact of Covid-19 on the banking industry by examining 121 documents from the Scopus database, including journals, book chapters, conference papers, and reviews. Background of Problems: The COVID-19 pandemic not only produces a crisis but also has the potential to alter the structure of the global economy, thereby influencing the banking industry and financial system. Novelty:  Conduct a comprehensive literature review by identifying the presence of GAP in research, as well as to assist future researchers in determining the development of research and in exploring further research on the impact of Covid-19 on the banking industry. Research Method : This research employs R-studio and biblioshiny software for text analysis. Findings/Result: The findings indicate that the COVID-19 pandemic has an impact on the banking business, which can be both a threat and an opportunity. In addition, this study includes a summary of the keywords that frequently appear in this topic and a summary of the most pertinent word analysis, word treemap, co-occurrence network, thematic map, and conceptual structure. Conclusion: Our findings inform regulatory authorities concerned with enhancing the financial stability of the banking sector to enhance their policies and banking practitioners to seek innovative tactics to compel banks to better align themselves with risks during the COVID-19 pandemic. In addition, this study reveals the existence of research gaps in order to provide future researchers with useful information.